Maneras cinematográficas de mirar - Casanova Varela, Basilio (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
We made in this article a brief and didactic route by four cinematographic ways to watch. We were centered for it in the analysis of four types of cinema: the classic cinema, the manierista cinema, the cinema of vanguard and the postclassic cinema